Kuasa Pengetahuan Perempuan dalam Pemenuhan Pangan Keluarga di Aceh - Nulwita Maliati; Nurjanius Situmorang; Ade Ikhsan Kamil (Department of Anthropology, 2026)
Indonesia continues to face challenges in food and nutrition fulfillment that lead to stunting, particularly in Pidie District, Aceh. This study aims to analyze the power of women's knowledge in family food fulfillment using Michel Foucault’s Power-Knowledge and Body Discipline theories. Using a qualitative approach, in-depth interviews were conducted with 40 families of stunted children and infants under two years old (baduta). The results reveal a dualism in knowledge construction: government knowledge, which promotes balanced nutrition through the